Predictive value of subendometrial – endometrial blood flow assessment by transvaginal 3D power doppler on the day of HCG on clinical outcome of IVF cycles - Choudhary, Manisha; Chowdhary, Jai; Swarankar, Mohan Lal; Bharadwaj, Shiv Lal (International Journal of Research in Medical Sciences, 2017)
Background: The objective of the study was to evaluate the role of subendometrial-endometrial blood flow assessment by 3D Tran-vaginal Power Doppler in predicting pregnancy outcome in IVF-ET cycles. The study was a prospective, non-randomized clinical study. Methods: A total of 107 infertile women undergoing their first IVF-ET cycle with good response were taken for study (From March 2014 to Nov 2014 at Jaipur Fertility Centre, ART unit of Mahatma Gandhi University of Medical Sciences & Technology). Women with Tubal factor, Male factor and unexplained infertility were included in the study. Those with past h/o Genital Koch’s and hypo menorrhea were excluded. Assessment of subendometrial-endometrial blood flow was done on the day of HCG with endometrial thickness ≥ 6.5mm by Tran-vaginal 3D- Power Doppler. Results: There was no significant difference in mean age, duration of infertility, BMI, cause of infertility, stimulation protocol, serological hormone levels, number of mature oocytes, number of good quality embryos and mean endometrial thickness on the day of HCG. According to Doppler study (3D-Power Doppler), women with blood flow to zones 1, 2 and 3 were categorized in to groups A (n=15), B (n=36) and C (n=56). Overall pregnancy rate was 32.71%. The clinical pregnancy rate was significantly higher in Group C in comparison of Group B and A (42.85% vs. 27.77% and 6.66%). Similarly implantation rate was also higher in group C (23.20% vs. 11.22% and 2.38%). Conclusions: The presence of good subendometrial-endometrial vascularity significantly improves pregnancy outcome in IVF-ET cycles in our study.